Reconstruction of Criminal Design Based on Strict Liability Theory for Hospitals in Cases of Medical Malpractice Against Patients - Prasetyo, Handoyo; Waluyo, Bambang; Subakdi, Subakdi; Roring, Edward Benedictus; Salles, Sergio (Jurnal Suara Hukum, 2024)
The increasing number of medical malpractice cases is ironic, because with the current Health Law it is hoped that malpractice cases can be reduced in number. The Health Law and other regulations must be obeyed by all parties in the world of health, especially hospital corporations so that apart from medical personnel or health workers, hospitals, directors and hospital management must also take legal responsibility, in accordance with their respective roles in the event of malpractice in the hospital environment. On the other hand, the stakeholders of this hospital will receive legal protection if they have implemented all their rights and obligations in accordance with applicable legal provisions. The specific purpose of this research is to prove that hospital corporations are also eligible for criminal sanctions if malpractice occurs in the hospital environment, through the application of strict liability principle, compiled with the interconnection of various related legislation products. This research uses normative juridical research methods that are descriptive prescriptive, using data and information from relevant literature sources, primary legal sources in the form of statutory provisions and jurisprudence, corporate theories used to analyse the problems, as well as research data obtained from the internet/website of related agencies. Keywords: hospitals, liability, malpractice